PENGGUNAAN MODEL KOOPERATIF TIPE TPS (THINK PAIR SHARE) PADA PEMBELAJARAN TRIGONOMETRI DALAM UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK - Nandang Arif Saefuloh; Yayu Laila Sulastri; Agus Salim (UJMES (Uninus Journal of Mathematics Education and Science), 2019)
The optimum portion of learning activities of students in a learning becomes urgent given to students, with the ultimate goal of obtaining the expected learning outcomes. However, the reality that occurs, the learning process often marginalizes the activities of students, one of the causes of this problem is the learning process that is fixed on the old pattern, namely the one-way learning process, from the teacher to the students, the teacher carries out learning by ignoring the optimization of participants' learning activities students, learning activities of students are only limited to listening and or taking notes. In other words, the teacher is active while the child is receptive. So that learning outcomes are expected to be at a low level or may not be achieved at all. This research is a Classroom Action Research (CAR/PTK), PTK is defined as a teacher's measured and systematic effort to solve problems that arise in learning events in his class, as well as to determine the quality of the process and learning outcomes of students. Solving these problems is done inclusive in the implementation of learning that is practical, situational, conditional, and contextual. The conclusion of this study is that cooperative model of TPS type can relatively improve student learning activities, cooperative model of TPS type can relatively improve student learning outcomes, and learning by using cooperative model of TPS type obtain positive responses from students.